Dimethyloxalylglycine treatment of brain-dead donor rats improves both donor and graft left ventricular function after heart transplantation - Hegedűs, Péter; Li, Shiliang; Korkmaz-İçöz, Sevil; Radovits, Tamás; Mayer, Tobias; Al Said, Samer; Brlecic, Paige; Karck, Matthias; Merkely, Béla; Szabó, Gábor (The journal of heart and lung transplantation, 2016)
Objective - Hypoxia inducible factor (HIF)-1 pathway signalling has a protective effect against ischemia/reperfusion injury. The prolyl-hydroxylase inhibitor dimethyloxalylglycine (DMOG) activates the HIF-1 pathway by stabilizing HIF-1α. In a rat model of brain death (BD)-associated donor heart dysfunction we tested the hypothesis that pre-treatment of brain-dead donors with DMOG would result in a better graft heart condition. - Methods - BD was induced in anesthetized Lewis rats by inflating a subdurally placed balloon catheter. Controls underwent sham operations. Then, rats were injected with an intravenous dose of DMOG (30 mg/kg) or an equal volume of physiologic saline. After 5 hours of BD or sham operation, hearts were perfused with a cold (4°C) preservation solution (Custodiol; Dr. Franz Köhler Chemie GmbH; Germany), explanted, stored at 4°C in Custodiol, and heterotopically transplanted. Graft function was evaluated 1.5 hours after transplantation. - Results - Compared with control, BD was associated with decreased left ventricular systolic and diastolic function. DMOG treatment after BD improved contractility (end-systolic pressure volume relationship E’max: 3.7 ± 0.6 vs 3.1 ± 0.5 mm Hg/µ1; p < 0.05) and left ventricular stiffness (end-diastolic pressure volume relationship: 0.13 ± 0.03 vs 0.31 ± 0.06 mm Hg/µ1; p < 0.05) 5 hours later compared with the brain-dead group. After heart transplantation, DMOG treatment of brain-dead donors significantly improved the altered systolic function and decreased inflammatory infiltration, cardiomyocyte necrosis, and DNA strand breakage. In addition, compared with the brain-dead group, DMOG treatment moderated the pro-apoptotic changes in the gene and protein expression. - Conclusions - In a rat model of potential brain-dead heart donors, pre-treatment with DMOG resulted in improved early recovery of graft function after transplantation. These results support the hypothesis that activation of the HIF-1 pathway has a protective role against BD-associated cardiac dysfunction.